Harnessing TikTok's Marketing Potential: A Case Study of @KUCA.OFFICIAL's Communication Strategy in Inspiring Consumer Purchase Intentions: - Nathaniel Bryan; Silvanus Alvin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research explores the marketing potential of TikTok in Indonesia, focusing on the case study of @KUCA.OFFICIAL, a brand specializing in gaming chairs. With TikTok's rapid popularity growth in Indonesia and its 113 million users, businesses are recognizing its vast marketing potential. The qualitative case study method is used, involving interviews, observations, and document analysis. The study highlights the brand's effective use of the marketing mix (4Ps) – product strategy with diverse designs, pricing strategy through discounts, interactive promotion strategy, and a distribution approach combining offline and online presence. This research provides valuable insights for businesses seeking to leverage TikTok for effective marketing in Indonesia.